Pengaruh Media Sosial Terhadap Pemahaman Tentang Konsep Sosial Dan Budaya di SDN Sumingkir 02 - Gigih Winandika; Widiawati Widiawati; Lili Kurniasih; Rahil Nur Fadhilah; Resa Dwi Septina; Vinna Salsabila Yulia; Suci Islami (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study uses a descriptive qualitative approach to investigate how social media use impacts students’ understanding of social and cultural concept at SDN Sumingkir 02. The research subject are students in grades V and VI who actively use social media. To collect data, observation, semi-structured interviews, and documentation were used. According to the research findings, various aspects of students lives are influenced by social media including learning behavior, social interactions, and communication patterns. Student interact more digitally than face to face, which can recude the quality of social relationships and increase risks such as anxiety, stress, and cyberbullying. Social media has positive benevits, such as increasing creativity and cultural knowledge, but excessive use without supervision can interfere with the development of students character and mental health. Therefore, parents and teachers must play an active role in guiding their students and improving their digital literacy.